A Sintering Ore Blending Optimization Model Based On "Iron Increase and Silicon Reduction" Ore Dressing Processes - Cheng-song Liu; Jing-she Li; Hai-yan Tang; Wei Liu (The Minerals, Metals and Materials Society, 2014)
"In order to effectively utilize cheap and low quality iron ores, a hematite ore in a certain steel plant in Xinjiang was researched on to obtain ""iron increase and silicon reduction"" by ore dressing operation experiment and the performance indexes of the hematite ore were optimized. Based on the fundamental characteristics and high-temperature properties of the concentrate after ore dressing and other five kinds of iron ores which were co=only used in this steel plant, ore matching principles were proposed and a sintering ore blending optimization model was established. Finally, sinter pot test was carried out to verify the validity and practicability of the sintering ore blending optimization model which was aimed at giving consideration to the sintering indexes and the cost.IntroductionIn recent years, the price of imported iron ore with high quality is always at a high level, while iron ore self-sufficient rate in China is less than 50%. Enormous market demand and high dependence of domestic enterprises on imported iron ore makes the price of it hardly return to rational. In order to get rid of the situation of long-term meager profit and even deficit, more and more iron and steel enterprises in China transit their focus of reducing production cost to the utilization and development of relatively cheap but low-grade iron ore resources at home[l-4l_ However, besides the disadvantages of low iron grade, high content of impurities and complex embedded properties, the high-temperature properties of iron ore often go beyond the suitable ranges for producing sinter with high quality. Thus directly utilization of this kind of iron ore without ore dressing process would probably affect the metallurgical performance and indexes of sinter ore.Previous research and production practice have shown that traditional iron ore matching in sintering mainly focus on the reasonable collocation of properties of iron ores with low quality and high quality, but pay less attention to ore dressing process of low quality iron ores and matching them with high quality iron ores. Actually, compare with directly utilization, iron ores with low quality after ore dressing have higher suitability for matching with high quality ones which is beneficial to reduce the consumption of iron ores with high quality and control the production cost of sintering [5-s1."